Daniel H. Pink. Drive: The Surprising Truth About What Motivates Us. Riverhead Books, U.S. 2009. 256 page. (Hardbound). (The Pakistan Development Review, 2020)
Daniel Pink points out that Encarta was developed by a of well-paid team by Microsoft as a flagship project, but it lost out to Wikipedia that was developed by people without payment. Modern human resource management (HRM) emerged in the industrial revolution and was based on extrinsic motivations—“carrots and sticks” such as “if you do this, you get that consequence”. Thus, promotions in a hierarchy were offered as were bonuses and salary increase and some non-cash advantages for work well done. In the opposite case, instruments were reprimands, denial of promotions, bonuses and benefits and in the worst case “fired from the job”. He calls these extrinsic motives because they are defined by the system with little involvement of the individual.